Physical and Chemical Research Methods of Lightweight Concrete - Shakirov, Tuygun; Yusupov, Usmonjon; Khasanov, Bakhrom (International Journal of Psychosocial Rehabilitation, 2020)
This research paper discusses the physicochemical and microscopic methods for studying the influence of porous aggregate micro-filler on improving the structure formation of lightweight concrete composition and the effect on lightweight concrete construction and technical properties of a filler consisting of quartz porphyry and carbonized clay.